Teachers' beliefs about social-emotional learning: Identifying teacher profiles and their relations with job stress and satisfaction. (October 2015) - Collie, Rebecca J.; Shapka, Jennifer D.; Perry, Nancy E.; Martin, Andrew J.
Abstract: This study examines the extent to which teachers may be grouped based on their beliefs about social-emotional learning (SEL). SEL is aimed at promoting students' social and emotional competencies (e.g., responsible decision making, social awareness). Research suggests that in addition to being relevant to student outcomes, SEL is also relevant to teachers' experiences at work. We utilized latent profile analysis to identify profiles of teachers based on three different beliefs—comfort with SEL, commitment to improving SEL skills, and perceptions of principal and school-wide support for SEL. Findings revealed three different profiles—the SEL-thriver, SEL-striver, and SEL-advocate—that have differential levels of comfort and perceived support for SEL, but not commitment for SEL. Findings also demonstrated that the profiles were associated with differences in several socio-demographic characteristics and two outcomes—teacher stress and job satisfaction. Combined, the findings have implications for teachers as well as students and schools. Highlights: We examined teachers' beliefs about social-emotional learning (SEL). We identified three teacher profiles that differed in terms of their SEL beliefs. Profiles were associated with different teacher characteristics. Profiles also differed with respect to levels of stress and job satisfaction.